Brecciation of glacially overridden palaeokarst (Lower Aare Valley, northern Switzerland): result of subglacial water‐pressure peaks?. (22nd July 2020) - Gegg, Lukas; Buechi, Marius W.; Ebert, Andreas; Deplazes, Gaudenz; Madritsch, Herfried; Anselmetti, Flavio S.
Abstract : Water pressures at the base of active glacial overdeepenings are known to fluctuate strongly on various time scales. Rapid peaks in basal water pressure can lead to fracturing of the glacier bed, a process that has been described at numerous sites around the world, mostly based on large hydrofracture systems. This article presents drill‐cores from the base of a >100‐m‐deep glacial overdeepening in the Lower Aare Valley in northern Switzerland that were investigated with high‐resolution imaging (including X‐ray computed tomography) as well as compositional and microstructural analyses. The drill‐cores recovered Jurassic limestones hosting palaeokarst voids infilled with blue clay. We identify this clay, based on its kaolinitic composition, as siderolithic Bolus Clay but in a rather atypical variety formed under reducing conditions. The surfaces of the palaeokarst walls show smoothly undulating as well as brecciated sections with form‐fit interlocking clasts, which are the result of an in situ brecciation process. We argue that these particular fractures are not related to (glacio‐)tectonics or frost action. Instead, we suggest an explanation by involving water‐pressure peaks that were transmitted to the void walls by the clayey karst filling, resulting in hydrofracturing. In addition to pervasive karstification and tectonic overprinting, this water pressure‐driven fracturing may have enhanced the deep incision of the overdeepening into the rheologically competent bedrock.